Understand Variance in Math

Understand Variance in Math

The variance measures the dispersion of a random variable, which is the expectation of the squared difference between each data point and the expectation.

$$ Var(X) = E[(X - E[X])^2] $$

The variance \(Var(X)\) is also written as \(\sigma^2\), where \(\sigma\) is the standard deviation.

Equivalent Formula #

Variance is the expectation of the square of each data point minus the square of the expectation.

$$ Var(X) = E[X^2] - E[X]^2 $$

Why? Because of the standard definition:

$$ E[(X - E[X])^2] = E[X^2 - 2XE[X] + E[X]^2] $$

According to the linearity property of expectation (i.e., each part can be calculated separately):

$$ E[X^2 - 2XE[X] + E[X]^2] = E[X^2] - 2E[X]E[E[X]] + E[X]^2 $$

Among them, \(E[X]\) is a constant, so \(E[E[X]] = E[X]\). Finally, we get:

$$ E[X^2] - 2E[X]E[X] + E[X]^2 = E[X^2] - E[X]^2 $$

This equivalent formula is more convenient when calculating the variance of some distributions.

Multiplication #

For any constant \(a\) and random variable \(X\), the variance changes with the square of the constant, because the variance itself is squared.

$$ Var(aX) = a^2 Var(X) $$

How to prove it? First, because the expectation calculation is linear:

$$ E[aX] = aE[X] $$

So:

$$ \begin{align} Var(aX) &= E[(aX - E[aX])^2] \\ &= E[(aX - aE(X))^2] \\ &= E[a^2(X - E(X)^2] \\ &= a^2E[(X - E(X))^2] \\ &= a^2Var(X) \end{align} $$

Addition #

For two random variables \(X\) and \(Y\), we have:

$$ Var(X + Y) = Var(X) + Var(Y) + 2Cov(X, Y) $$

Where \(Cov(X, Y)\) is the covariance of \(X\) and \(Y\), indicating the linear relationship between \(X\) and \(Y\).

Why? First, expand according to the definition of variance:

$$ Var(X + Y) = E[(X + Y - E[X + Y])^2] $$

According to the linearity property of expectation:

$$ E[X + Y] = E[X] + E[Y] $$

So:

$$ \begin{align} Var(X + Y) &= E[(X + Y - E[X] - E[Y])^2] \\ &= E[((X - E[X]) + (Y - E[Y]))^2] \end{align} $$

Expand the square term:

$$ Var(X + Y) = E[(X - E[X])^2 + 2(X - E[X])(Y - E[Y]) + (Y - E[Y])^2] $$

Still, the expectation is linear, so it can be calculated separately:

$$ Var(X + Y) = E[(X - E[X])^2] + 2E[(X - E[X])(Y - E[Y])] + E[(Y - E[Y])^2] $$

Among them:

  1. \(E[(X - E[X])^2] = Var(X)\)
  2. \(E[(Y - E[Y])^2] = Var(Y)\)
  3. \(E[(X - E[X])(Y - E[Y])] = Cov(X, Y)\) this is the covariance of \(X\) and \(Y\).

So we get:

$$ Var(X + Y) = Var(X) + Var(Y) + 2Cov(X, Y) $$

If \(X\) and \(Y\) are independent, then their covariance, i.e., \(Cov(X, Y)\) is 0, then:

$$ Var(X + Y) = Var(X) + Var(Y) $$

If it is two identical random variables \(X\)? Equivalent to the multiplication case, we have:

$$ Var(X + X) = Var(2X) = 4Var(X) $$

That is, the same random variable is superimposed, and the discrete degree will increase.